Native parasitoids of Rhagoletis pomonella Walsh (Diptera: Tephritidae) in hawthorn in central Mexico - Muñiz-Reyes, Erica; Lomelí-Flores, J. Refugio; Sánchez-Escudero, Julio (Instituto de Ecología, A.C., 2011)
Rhagoletis pomonella is one of the main pests of hawthorn in central Mexico. This pest can damage 100% fruit when no control tactics are applied. A survey from 2007 to 2009 in Texcoco, Mexico, was held in order to explore the natural enemy complex of this pest. Puparia of Rhagoletis pomonella were collected in soil from infested hawthorn trees. Puparia were kept under controlled conditions during diapause awaiting for parasitoid emergence. 2734 puparia were collected, but only 1460 insects emerged: 68.3% of them were fruit flies and 31.7% were parasitoids. Six parasitoid species were identified: Coptera sp. (Diapriidae), the most common parasitoid (25% of total parasitism), represents a new record of this species attacking R. pomonella pupae. Utetes near canaliculatus (Braconidae) (3.4%) was previously recorded as a parasitoid of this fruit fly in Mexico; Diachasmimorpha mexicana (Braconidae) (2.3%) had not been reported for this area.. Hemipenthes blanchardiana (Bombyliidae) (<0.5%) represents the first record of this family attacking R. pomonella worldwide. Finally, an individual Ichneumonidae and Braconidae were found, but these were not identified. Total parasitism was 31.7%, this result can generate a potential for the use of these parasitoids in conservation biological control programs.